MINAT SISWA DALAM MENGIKUTI PEMBELAJARAN PENDIDIKAN JASMANI SELAMA PANDEMI COVID 19 DI SMA NEGERI 4 PEKANBARU - Rahmat Hidayat; Ardiah Juita; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research generally aims to find out students' interest in taking physical education lessons during the covid 19 pandemic at SMA NEGERI 4 PEKANBARU. The population in this study were all students of class XI IPA who took physical education lessons at SMA NEGERI 4 PEKANBARU in 2021 which consisted of XI IPA 1 to XI IPA 4, totaling 90 students. The data collection technique uses a questionnaire instrument through the google form. The analysis technique used is to pour the frequency into the form of a percentage. The results of this study indicate that students' interest in participating in Jamsni education learning during the covid 19 pandemic at SMA NEGERI 4 PEKANBARU is moderate. NEGERI 4 PEKANBARU is moderate with the consideration that the highest frequency is in the “Medium” category. This is indicated by the percentage of 36.7% (33 students).Key Words: Interest, Learning, Physical Education, Covid19 Pandemic.